2020
DOI: 10.3389/fncel.2020.00106
|View full text |Cite
|
Sign up to set email alerts
|

Function of P2X4 Receptors Is Directly Modulated by a 1:1 Stoichiometric Interaction With 5-HT3A Receptors

Abstract: Interacting receptors at the neuronal plasma membrane represent an additional regulatory mode for intracellular transduction pathways. P2X4 receptor triggers fast neurotransmission responses via a transient increase in intracellular Ca 2+ levels. It has been proposed that the P2X4 receptor interacts with the 5-HT 3 A receptor in hippocampal neurons, but their binding stoichiometry and the role of P2X4 receptor activation by ATP on this crosstalking system remains unknown. Via pull-down assays, total internal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…While it would be interesting to see the extent of P2X–NMDAR inhibition at lower concentrations, such as EC 10-20 ., such studies are out of the scope of this current work. However, it is important to note that non-additive interactions between P2X2 and 5-HT 3A have been, reported at both low and saturating agonist concentrations [ 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it would be interesting to see the extent of P2X–NMDAR inhibition at lower concentrations, such as EC 10-20 ., such studies are out of the scope of this current work. However, it is important to note that non-additive interactions between P2X2 and 5-HT 3A have been, reported at both low and saturating agonist concentrations [ 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…P2X cross-talk can rely on physical interactions between the intracellular domains of the two different receptors and may also regulate the subcellular targeting of receptors in neurons. Cross-talk between several P2X subtypes has been shown to modulate the activity of GABA-A receptors [ 17 , 18 , 19 , 20 ], nicotinic ACh receptors [ 21 ] and 5-Hydroxytryptamine Receptor 3A (5-HT 3A ) [ 22 , 23 , 24 ]. Alternatively, P2X can also have slow but long-lasting modulatory effects on the function or surface trafficking of receptors; activation of post-synaptic P2X by ATP released from glia has been shown to trigger changes in the surface trafficking of α-amino-3-hydroxy-5- methyl-4-isoxazolepropionic acid receptors (AMPAR), which leads to long lasting changes in synaptic efficacy at glutamatergic synapses.…”
Section: Introductionmentioning
confidence: 99%
“…In the hippocampus, the activation of postsynaptic P2X2 or P2X4 triggers surface AMPAR internalization, leading to P2X-mediated long-term synaptic depression ( Pougnet et al, 2014 , 2016 ). P2X receptors further modulate the activity of GABAa receptors ( Boué-Grabot et al, 2004 ; Toulmé et al, 2007 ; Jo et al, 2011 ), nACh receptors ( Khakh et al, 2000 ), and 5-hydroxytryptamine receptor 3A ( Boué-Grabot et al, 2003 ; Emerit et al, 2016 ; Soto et al, 2020 ). Coexpression of P2X receptors and NMDARs in oocytes showed that they interact via the C-terminal domain of NMDAR, and their activation inhibits NMDAR-dependent currents ( Rodriguez et al, 2020 ).…”
Section: The Nmdar Surface Cis-interactome: Current Viewmentioning
confidence: 99%